To Error Problem Concerning Measuring Concentration of Carbon Oxide by Thermo-Chemical Sen - V. I. Nazarov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper gives additional errors in respect of measuring concentration of carbon oxide by thermo-chemical sensors. A number of analytical expressions for calculation of error data and corrections for environmental factor deviations from admissible ones have been obtained in the paper